EFFORTS TO INCREASE THE MARKET FOR PULI CRACKER PRODUCTS THROUGH REBRANDING AND HALAL CERTIFICATION - Rusdi, Muhammad Iqbal; Faradiba, Vanisa Reyhan; Putri, Dian Puspita Salsabilla; Harsono, Budwi (Antis-publisher, 2024)
General Background: Micro, Small, and Medium Enterprises (MSMEs) are vital to economic development, yet many face challenges in expanding their market reach. Specific Background: The Puli Cracker MSME, owned by Mrs. Makilah, exemplifies this challenge, as it primarily relies on local orders without strategies for broader market expansion. Knowledge Gap: A lack of business development skills, particularly in product packaging, branding, and certification, hinders the potential growth of many small businesses like Mrs. Makilah's. Aims: This community service project aims to assist the Puli Cracker MSME in creating packaging stickers, improving product packaging, and obtaining halal certification to enable market expansion beyond the local community. Results: Through interviews and observations, the project identified key areas for improvement, including product labeling, packaging redesign, and halal certification registration. The implementation stages included creating packaging stickers, repackaging the crackers, and fulfilling halal certification requirements, all of which positively impacted the business. Novelty: The project introduced a structured, step-by-step approach to MSME development, combining product enhancement with halal certification, which is often overlooked in small-scale enterprises. Implications: The improvements in packaging and branding, along with the halal certification, are expected to significantly enhance the marketability and credibility of Mrs. Makilah’s Puli Cracker, allowing it to reach a wider market. These interventions provide a replicable model for other MSMEs aiming to grow sustainably and expand their market share.